Sustainable transport development, innovation and technology : proceedings of the 2016 TranSopot Conference - Suchanek, Michał (Springer proceedings in business and economics,, 2017)
This proceedings volume presents current research on transport sector development, with particular emphasis on sustainable transport development, innovation and transport enterprise growth and survival. Derived from the 2016 TranSopot Conference held in Sopot, Poland, this book aims to show the possibilities of maximizing the efficiency of transport, while keeping the negative effects at a sustainable level. Transport is an important field of human activity, both from economic and social points of view. It has been proven that the development of transport contributes to the development of regional, national and international economic relations. Currently, the three most important topics in transportation research are green transport, transport innovations and metropolitan transport. These are the areas in which the contributions presented in this book are focused. Researchers in the field of sustainable transport provide the reader with a comprehensive description of possible activities towards green transport both in the terms of various transport branches and in the supply chain as a whole. This is the framework of the second field of transport research -- innovation. The authors present a wide array of a technological, organizational, process and marketing innovation, which allow transport organizers and operators to provide service in a safe, sound and economically favorable way. The analysis of these innovations and the practical implications of their introduction should be a worthwhile experience both for the transport researchers and for the transport business practitioners. Lastly, the book reflects the tendencies of rapid development in urban and metropolitan areas which forces transport policy makers to provide citizens with a comfortable and faster way of commuting that doesn't result in unacceptable congestion or other negative effects. Different concepts of metropolitan transport management are presented and their effect on the transport systems is also investigated.